ANALISIS PENGARUH MANAJEMEN LABA SEBELUM IPO TERHADAP KINERJA PERUSAHAAN - Gusrida Juwita Limbong; Daljono Daljono (Diponegoro Journal of Accounting, 2014)
The corporate perform IPO to get any additional  fund for corporate development. In order to attract the investors, manager can report higher profit that said  as earning management. The purpose of this study is to investigate earnings management during periods before the Initial Public Offering date. This study also examine the  effect of earning management to post-issue underperformance in  earning and market. Sample of the study consists 36 IPO companies in the agricultural sector, mining, and manufacturing during 2001 – 2009. Earning management is measure with discretionary accrual from modified Jones model. The data is collected from Prospektus and yearly financial report of the company. One sample t test is used to examine whether significant positive discretionary accrual among the companies before the IPO date and regression analysis is used to examine the effect of earning management to the post-issue underperformance in  earning and stock return. The results of the study indicate the earning management before the IPO date, but do not show the same pattern in the two years before IPO date. Earning management before the IPO date has negatively effect to underperformance in earning for the first and second year after IPO, but earning management do not significantly effect to the third year underperformance in earning after IPO. Earning management before the IPO date has negatively effect to stock return during three years.